Namghar as Socio-Religious Institution: Heritage, Contemporary Relevance, and Evolving Social Status - Lamba, Pragya (Journal of Social Science and Humanities, 2025)
Food, possessions and shelter are the basic needs of the entire human species. Once such needs are met, people strive for intellectual, spiritual and other excellence. But wherever the Assamese Vaishnavas live permanently or temporarily, they are not satisfied unless they can establish a Namghar personally or socially along with these triple needs. The founders of all the major religions in the world establish an institution or house of worship as a place of worship and engage in all aspects of religion there. Everyone's house of worship has a different name.